Toxin‐Enabled "On‐Demand" Liposomes for Enhanced Phototherapy to Treat and Protect against Methicillin‐Resistant Staphylococcus aureus Infection (Small 35/2022). Issue 35 (1st September 2022) - Zhuge, Deli; Chen, Mengchun; Yang, Xuewei; Zhang, Xufei; Yao, Lulu; Li, Li; Wang, Haonan; Chen, Hao; Yin, Qingqing; Tian, Dongyan; Weng, Cuiye; Liu, Shuangshuang; et al.
Abstract : MRSA Phototherapy In article number 2203292, Weiliang Xia, Yingzheng Zhao, Yijie Chen, and co‐workers show that Van‐Lipo(IR780)‐PFC (an oxygen‐carrying perfluorocarbon nanoemulsion stabilized by a vancomycin‐functionalized sphingo‐myelin liposome loaded with IR780) can capture methicillin‐resistant Staphylococcus aureus (MRSA) toxins in situ, resulting in the on‐demand release of phototherapeutic agents, thus improving the specificity of photothermal therapy/photodynamic therapy under near‐infrared irradiation. Meanwhile, pore formation upon the insertion of toxins into the nanoparticles results in the generation of vaccines in situ, thus leading to an anti‐MRSA immune response.